Employee Performance ; Intrinsic Motivation, Innovational Cilmate, Incentives, and Transformational Leadership - Agus Dharmanto (Dinasti International Journal of Management Science, 2023)
The purpose of the study wants to prove and strengthen the results of existing research related to variables used in literature studies from reputable national journal sources and reputable international journals, qualitative research methods with literature review of scientific articles derived from reputable international journals and national reputation, by looking for evidence to corroborate. Evidence from several scientific articles found related to the variables of this study, all of them have a positive and significant influence, and a strengthen the results of past research by adding to the treasures of the results of this study with the variables used. Recommendations for other researchers in the future, then use the differentiating variables found by the researcher to be used in future research using different research methods and objects in the field of human resource management.